2018
DOI: 10.1093/jcag/gwy056
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inflammatory Bowel Disease in Canada 2018: Children and Adolescents with IBD

Abstract: Canada has among the highest rates of childhood-onset IBD in the world. Over 7000 children and youth under 18 years old are living with IBD in Canada, and 600 to 650 children under 16 years old are diagnosed annually. While the peak age of onset of IBD is highest in the second and third decades of life, over the past two decades incidence has risen most rapidly in children under 5 years old. The treatment of children with IBD presents important challenges including therapeutic choices, risk of adverse events t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
90
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 100 publications
1
90
0
5
Order By: Relevance
“…To what extent this difference also results in future lost life chances (eg not as good educational results and less well‐paid employments as would have been expected) and reduction in lifetime earnings is yet to be shown. More importantly, many studies have also shown that patients with IBD, regardless of age of diagnosis, have more work loss (sick leave and disability pension) than matched reference individuals or IBD‐free siblings 4‐9 ; these observations to us suggests that it is the disease itself, with its remitting and relapsing disease course, rather than the (limited) reduction in adult height that causes reduced lifetime earnings. That is, if lifetime earnings are indeed reduced, which is yet to be shown (although we agree it is likely).…”
mentioning
confidence: 76%
“…To what extent this difference also results in future lost life chances (eg not as good educational results and less well‐paid employments as would have been expected) and reduction in lifetime earnings is yet to be shown. More importantly, many studies have also shown that patients with IBD, regardless of age of diagnosis, have more work loss (sick leave and disability pension) than matched reference individuals or IBD‐free siblings 4‐9 ; these observations to us suggests that it is the disease itself, with its remitting and relapsing disease course, rather than the (limited) reduction in adult height that causes reduced lifetime earnings. That is, if lifetime earnings are indeed reduced, which is yet to be shown (although we agree it is likely).…”
mentioning
confidence: 76%
“…However, these paediatric guidelines were based on an expert opinion from evaluation of the literature without using GRADE methodology ( 12 ). Further, special cohorts including individuals who are actively in the process of transferring to adult care, pregnant women, and the elderly need to be taken into consideration ( 31 , 39 , 40 ). Given the lack of published data, it may be prudent to delay switching in individuals who are in the process of transferring from paediatric to adult care ( 41 ), as many other changes are already occurring, including change in physician, hospital, clinic and insurance.…”
Section: Biosimilar Switching In Vulnerable Populationsmentioning
confidence: 99%
“…[1] It has a higher incidence in Canada and reports of more difficult treatments. [2][3][4] Clinically, this type of patients has a slow treatment effect and a long treatment period, which have attracted the attention of gastrointestinal physicians and need expensive costs [4] . The disease is considered a patient's immune system disorder, and changes in the intestinal flora and its metabolites usually affect the patient's immune system, thereby inducing the disease.…”
Section: Introductionmentioning
confidence: 99%